Remodelamento vascular em artérias mesentéricas de resistência de camundongos diabéticos db/db - Souza, Flavia Moreira (2009)
Little is known about Type 2 diabetes-induced structural remodeling of mesenteric resistance arteries. This study compared structural differences in small mesenteric resistance arteries in diabetic (db/db) and control (Db/db) mice. Vessels were isolated from 16wks old mice and structural properties were assessed by pressure myography. Mean arterial pressure (MAP) was measured in vivo by telemetry. The animals were treated for 4 wks with antioxidants Tempol or apocynin or with AT-1 receptor blocker candesartan. Western blot analysis was used to assess the expression of matrix regulatory proteins. MAP was similar between all the groups studied. Fasting blood glucose levels were higher in db/db mice (505±28 mg/dl) vs. control (115±10, p<0.001). The lumen diameter and media cross-sectional area were significantly increased in db/db compared to control suggesting hypertrophic outward remodeling. Cross-sectional compliance was significantly larger in the diabetic arteries. The stress-strain curve was shifted to the right in mesenteric arteries from diabetic mice compared with controls. Neither one of the treatments were able to change the remodeling presented by the db/db mice, as well as compliance and stress-strain relationship. The expression of the matrix regulatory proteins MMP-9, MMP-12, TIMP-1, TIMP-2, TGF-β and PAI-1 were increased in db/db arteries, while MMP-2 expression was not different between the groups. These data suggest that diabetic mesenteric resistance arteries undergo hypertrophic outward remodeling, increased vessel compliance and reduced stiffness that was associated with extracellular matrix turnover secondary to an imbalance between pro and anti-fibrotic factors. Neither the oxidative stress nor the pathways of angiotensin II in type II diabetes were involved at the remodeling or structural changes presented by diabetic db/db mice with 16wks of age treated for 4 wks.